Medicine and masculinity in the 19th century: transnational trends and the specificities of south-western Europe (Spain and France) - Martykánová, Darina; Gilarranz, Ainhoa; Núñez-García, Víctor M. (Dějiny – teorie – kritika, 2023)
Gender played an important role in the presentation of the medical profession in the 19th century. Medical historians point to the fact that the field of medicine became significantly masculinized from the early modern period onwards. The professionalisation of medicine, i.e., the widespread idea that medical treatment should be performed by people with professional training who charge money for their services, contributed to the exclusion of women from the role of medical authority. Another factor which played a role was the institutionalisation of medicine, i.e., the creation of new hospitals, job positions for physicians and surgeons, the establishment of medical chambers and the ultimate link between the medical profession and formal professional education. For several years, our team of authors has been studying the professional dynamics of medicine in Spain and France and comparing them with other countries. We have concluded that while gender played an important role in medical professional discourse and in the public image of doctors as we find it in the period press, cartoons, literature, and other forms of representation, it did not always happen in the same way everywhere. For example, there were significant differences between France, the UK and Spain in the manner, in which doctors and society used gender elements to reinforce doctors' authority or, conversely, to criticise it. Certainly, one could also trace differences and similarities when comparing with Central Europe. We hope that our theoretical reflections and practical analysis of the relationship between social class, masculinity, and expert identity of physicians in 19th century France and Spain will be of use to all.